Harnessing genomics to improve outcomes for women with cancer in India: key priorities for research. Issue 2 (February 2018) - Sundar, Sudha; Khetrapal-Singh, Poonam; Frampton, Jon; Trimble, Edward; Rajaraman, Preetha; Mehrotra, Ravi; Hariprasad, Roopa; Maitra, Arindam; Gill, Paramjit; Suri, Vanita; Srinivasan, Radhika; Singh, Gurpreet; et al.
Summary: Cumulatively, breast, cervical, ovarian, and uterine cancer account for more than 70% of cancers in women in India. Distinct differences in the clinical presentation of women with cancer suggest underlying differences in cancer biology and genetics. The peak age of onset of breast and ovarian cancer appears to be a decade earlier in India (age 45–50 years) than in high-income countries (age >60 years). Understanding these differences through research to develop diagnosis, screening, prevention, and treatment frameworks that ar e specific to the Indian population are critical and essential to improving women's health in India. Since the sequencing of the human genome in 2001, applications of advanced technologies, such as massively parallel sequencing, have transformed the understanding of the genetic and environmental drivers of cancer. How can advanced technologies be harnessed to provide health-care solutions at a scale and to a budget suitable for a country of 1·2 billion people? What research programmes are necessary to answer questions specific to India, and to build capacity for innovative solutions using these technologies? In order to answer these questions, we convened a workshop with key stakeholders to address these issues. In this Series paper, we highlight challenges in tackling the growing cancer burden in India, discuss ongoing genomics research and developments in infrastructure, and suggest key priorities for future research in cancer in India.